2022
DOI: 10.1136/bmjopen-2022-064352
|View full text |Cite
|
Sign up to set email alerts
|

Are workplace factors associated with employee alcohol use? The WIRUS cross-sectional study

Abstract: ObjectivesSociodemographic predictors of employee alcohol use are well established in the literature, but knowledge about associations between workplace factors and alcohol use is less explored. The aim of this study was to explore whether workplace factors were associated with employee alcohol use (consumption and alcohol-related problems).DesignCross-sectional study. Linear and binary logistic regression analyses.SettingHeterogeneous sample of employees (workers and supervisors) from 22 companies across geog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 92 publications
(200 reference statements)
1
1
0
Order By: Relevance
“…The key role of support from superiors and management staff in protecting the well-being of prison officers is highlighted in studies [60]. There are also studies showing that in other occupational groups, actively cooperating superiors are a protective factor against alcohol consumption for employees [61]. This is consistent with the result obtained in this study.…”
Section: O R I G I N a L P A P E Rsupporting
confidence: 90%
“…The key role of support from superiors and management staff in protecting the well-being of prison officers is highlighted in studies [60]. There are also studies showing that in other occupational groups, actively cooperating superiors are a protective factor against alcohol consumption for employees [61]. This is consistent with the result obtained in this study.…”
Section: O R I G I N a L P A P E Rsupporting
confidence: 90%
“…Hasegawa et al reported that in the working population, problem drinking was associated with occupational factors 10) . In other studies, work characteristics were shown to be linked to problem drinking [11][12][13] , and work-family status 14,15) and social activities 16) were also individually cited as related factors, suggesting differences in the factors related to problem drinking between men and women. However, these studies were cross-sectional and did not explain the causal relationship between these factors and problem drinking.…”
Section: Introductionmentioning
confidence: 85%